The impact of sowing time on corn yield capacity - Barabolia, O.; Kosenko, I. (Scientific Progress & Innovations, 2024)
The research was conducted as to studying the effect of sowing time on corn hybrids’ yield capacity under climate change. The investigation was made during 2021–2023 in field conditions of a farm in Pyriatyn territorial community of Poltava region. Mid-ripening DKC 3939 and DKC 4408corn hybrids were taken as the research objects. The preliminary study of weather conditions calculated by hydro-thermal moistening coefficient showed that April was humid enough, but insufficiently warm, which affected corn yield, sown on April 5. The yield of 84.7–98.5 hundredweight/ha for both hybrids was obtained, which was the lowest indicator in comparison with other sowing periods. However, the yield was higher than the average level in Ukraine (56.2–76.8 hundredweight/ha) and in Poltava region (64.5–85.1 hundredweight/ha). It has been substantiated that rather early corn seeding in insufficiently warmed soil extends the duration of the period from sowing to seedlings, and thus, the plant general vegetation, which decreases the yield. Seeding the corn on April 20 was more favorable and enabled to increase the yield capacity of DKC 3939 hybrid by 10.8–20.1 % (at the level of 95.3–110.7 hundredweight/ha), while that of DKC 4408 hybrid – by 3.0–14.0 % (89.1–112.3 hundredweight/ha). Moreover, DKC 3939 hybrid had higher yield than DKC 4408 when sown on April 20 in 2021 and 2023 – by 6.5 and 9.4 %, respectively. When sown on May 5, still higher yields for all the hybrids were received owing to favorable conditions at the beginning of growth and development (more warmed soil and sufficient soil moisture content). The yield of DKC 3939 hybrid was at the level of 98.7–112.4 hundredweight/ha (with the maximal indicator in 2023), while the yield of DKC 4408 hybrid was 93.2–114.5 hundredweight/ha (2022 was the most yielding). Thus, under unstable moistening and changeable temperature conditions, DKC 3939 hybrid turned out to be the most yielding when it was sown on May 5. The main factors affecting corn yields are sowing date and variety selection, including soil fertility, temperature and precipitation. The timing of sowing plays a key role in maximising corn yields and grain quality, as delayed sowing can lead to a linear decline in grain yields.